Clinical decision analysis in perinatology. (15th December 2017) - D'Souza, Rohan; Shah, Prakesh S.; Sander, Beate
Abstract: Clinical decision‐making in perinatology involves trade‐offs between two intricately related individuals – mother and fetus. Decision‐making in perinatology is challenging due to competing interests of the mother and the fetus. Although decision analytic methods are increasingly used to develop processes for clinical and cost‐effectiveness analyses in perinatology, there are no guidelines on the conduct and reporting of decision analysis studies that takes into account the complexities of the mother–fetus dyad. This article describes the basics of decision analysis and highlights areas that require special consideration in the perinatal context. It emphasizes the importance of obtaining patient preferences related to combined maternal‐fetal health states, stresses the relevance of both maternal and offspring health outcomes over appropriate time horizons, and explains challenges around the use of quality‐adjusted life years as an outcome measure in perinatology. It also provides insight into the complexities of dyad status in clinical and cost‐effectiveness analyses in perinatology.